PENGARUH LEARNING ORGANIZATION DAN KETERLIBATAN KERJA TERHADAP PERILAKU KERJA INOVASI PADA PT. JAMKRINDO CABANG MALUKU UTARA - Agustina Anreimi Yunus; Adnan Rajak; Ruslan Kamis (Jurnal Manajemen Sinergi, 2021)
Objective: The objectives of this study are: (1) To identify and analyze the effect of learning organization on innovative behavior; (2) Knowing and analyzing the effect of work involvement on innovative behavior; (3) Knowing and analyzing the influence of learning organization and work involvement simultaneously on innovative. Indonesian Credit Guarantee Limited The number of research samples was 33 employees. Methodology: The test tool used is multiple linear regression analysis using the statistical package for social scientists (SPSS) as a statistical test tool. Finding: H1, H2, and H3 accepted at the 5% confidence level.Conclusion: The results showed that: (1) Learning organization has a positive and significant effect on innovative behavior at Indonesian Credit Guarantee Limited North Maluku Branch .; (2) Job involvement has a positive and significant effect on innovative behavior at Indonesian Credit Guarantee Limited North Maluku Branch; (3) Learning organization and work involvement have a positive and significant effect simultaneously on innovative behavior at Indonesian Credit Guarantee Limited North Maluku Branch